2020
DOI: 10.1103/physrevaccelbeams.23.103101
|View full text |Cite
|
Sign up to set email alerts
|

Energy-resolved secondary-electron emission of candidate beam screen materials for electron cloud mitigation at the Large Hadron Collider

Abstract: Energy-resolved secondary electron spectroscopy has been performed on air-exposed standard Cu samples and modified Cu surfaces that are tested and possibly applied to efficiently suppress electron cloud formation in the high-luminosity upgrade of the Large Hadron Collider at CERN. The Cu samples comprise pristine oxygen-free, carbon-coated and laser-structured surfaces, which were characterized prior to and after electron irradiation and rare-gas ion bombardment. Secondary-electron and reflected-electron yield… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 81 publications
0
7
0
Order By: Relevance
“…In order to model the samples, for the microgeometry, the trench cross-sections and nanostructure SEM images were collected according to Bajek et al [22], and XPS data was recorded following the procedure reported by Bez et al [34] For deriving modelling parameters untreated samples were characterised, SEY data was collected for AR copper, Cu 2 O and CuO, sputter-cleaned copper and amorphous carbon. As well as SEY-energy spectrum data for AR copper, sputtercleaned copper and amorphous carbon according to Schulte et al [48] Lastly, angle-dependent SEY data was collected for sputter-cleaned copper.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to model the samples, for the microgeometry, the trench cross-sections and nanostructure SEM images were collected according to Bajek et al [22], and XPS data was recorded following the procedure reported by Bez et al [34] For deriving modelling parameters untreated samples were characterised, SEY data was collected for AR copper, Cu 2 O and CuO, sputter-cleaned copper and amorphous carbon. As well as SEY-energy spectrum data for AR copper, sputtercleaned copper and amorphous carbon according to Schulte et al [48] Lastly, angle-dependent SEY data was collected for sputter-cleaned copper.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The scaling variables are determined through recent SEY measurements of sputter-cleaned copper up to 50 0 incidence, illustrated in the supplementary material, and we assume that all emitted electrons follow a cosine angular distribution regardless of their energy. The emitted secondary electrons' energies are characterised by experimental SEY-energy spectrum data [48]. Then a particle tracking solver is used to record electron trajectories and the process is repeated on successive electron-matter interactions.…”
Section: Furman's Modelmentioning
confidence: 99%
“…While more accurate theories for low energy electron scattering are still to be explored, we have to rely on TEY measurements in this energy range. The latter, being a challenge on their own, have been performed mainly for materials that are used in space technologies by Balcon et al (2012) including for metals such as Cu by Schulte et al (2020), Ag, Au and crystalline silicon (c-Si) by Pierron et al (2017). Further experimental difficulties originate when performing such measurements on nonconductive surfaces prone to surface charging.…”
Section: Introductionmentioning
confidence: 99%
“…Low SEY materials or surfaces are aimed for reduction of surface charging of spacecrafts and satellites [1,2] as well as to mitigate formation of electron clouds in particle accelerators. [3][4][5][6][7] The primary electron energy dependence of the secondary electron yield as well as the kinetic energy distribution of the emitted electrons are subject of intensive studies since decades for elemental material surfaces and compounds [7][8][9][10][11][12][13][14][15][16][17] to accommodate the progressively developing technology demands. For many applications a SEY maximum below unity is sufficient to avoid cascade multiplication of the impinging electrons.…”
Section: Introductionmentioning
confidence: 99%